ANALYSIS OF PSYCHIATRIC NURSING CARE IN SCHIZOPHRENIC PATIENTS WITH APPLICATION OF OCCUPATIONAL THERAPY IN FREE TIME ACTIVITIES TO OVERCOME HALLUCINATIONS - Alfiya; Nur Hidaayah; Andikawati Fitriasari; Riska Rohmawati (Nurse and Holistic Care)
Introduction: Hallucinations are a mental health problem that is difficult to get rid of due to several factors such as socio-cultural where a person does not believe in his environment, causing anxiety and focusing on his hallucinations.